Peran Badan Pengawas Keuangan dan Pembangunan (BPKP) sebagai Keterangan Ahli Terhadap Penanganan Tindak Pidana Korupsi - Benny Karya Limantara (Universitas Bandar Lampung (UBL), 2016)
Financial Supervisory Agency (BPKP) as an internal auditor for the government increasingly felt by the citizens' demands for state officials who are clean and free of corruption, collusion and nepotism ( KKN ) as mandated by Law No. 28 of 1999 , and the demands on openness and good governance. BPKP is the Financial and Development Supervisory Agency which is a non-departmental institutions established by the President by Presidential Decree , so that BPKP is directly responsible to the President related to performance. The principal tasks of the Finance and Development Supervisory Agency ( BPKP ) is carrying out government duties in the field of financial supervision and development in accordance with the provisions of the legislation in force ( Article 52 of Presidential Decree No. 103 of 2001 on Status, Duties , Functions, Organizational Structure and Work Procedures of Non Departmental Government Institutions ).